2016
DOI: 10.1097/tp.0000000000001248
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rejection in Human Vascularized Composite Allotransplantation (Hand and Face Recipients)

Abstract: Vascularized composite tissue allografts (VCA) have become a viable option to restore severely damaged parts of the body that cannot be repaired with conventional surgical techniques. Acute rejection develops frequently in the early postgraft period both in human and experimental VCA, but the possibility of human VCA to undergo chronic rejection (CR) remained initially unknown. The experience gained over the years shows that, similar to solid organ transplants (SOT), human VCA can also develop CR. Chronic reje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 50 publications
(81 reference statements)
0
59
0
1
Order By: Relevance
“…10,11 Efforts to limit the use of immunosuppression or to transplant donor marrow without preconditioning to prevent these complications has led to acute rejection and even loss of the allograft. 1215 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Efforts to limit the use of immunosuppression or to transplant donor marrow without preconditioning to prevent these complications has led to acute rejection and even loss of the allograft. 1215 …”
Section: Introductionmentioning
confidence: 99%
“…in clinical morphology and histology of facial allografts distinct from those of NR and AR occurred in 3 of 7 facial transplant recipients. Indeed, prompt diagnosis and treatment of AR episodes are considered as a potential explanation for the low incidence of CR episodes across all VCA centers,3 although the time-course required for the eventual development of CR remains unknown.The first patient previously described in the literature developed T cell-mediated CR of the allograft after a programmed reduction of immunosuppressive therapy due to complications 11. Indeed, prompt diagnosis and treatment of AR episodes are considered as a potential explanation for the low incidence of CR episodes across all VCA centers,3 although the time-course required for the eventual development of CR remains unknown.The first patient previously described in the literature developed T cell-mediated CR of the allograft after a programmed reduction of immunosuppressive therapy due to complications 11.…”
mentioning
confidence: 99%
“…These are generally rapidly identified due in part to the high degree of immunological activity skin possesses making the first signs of rejection readily visible 20. While it was initially believed that chronic rejection would not be a significant issue, experience with more patients has demonstrated that, similar to other allografts, low-grade chronic rejection can occur 21. However, there is also no reason to believe that hand transplantation would be substantially different from solid organ transplantation when it comes to chronic rejection and long-term graft survival 5.…”
Section: Risks Of Hand Transplantationmentioning
confidence: 99%